Galectin-13/placental protein 13: redox-active disulfides as switches for regulating structure, function and cellular distribution. (7th October 2019) - Yang, Tong; Yao, Yuan; Wang, Xing; Li, Yuying; Si, Yunlong; Li, Xumin; Ayala, Gabriela Jaramillo; Wang, Yue; Mayo, Kevin H; Tai, Guihua; Zhou, Yifa; Su, Jiyong
Abstract: Galectin-13 (Gal-13) plays numerous roles in regulating the relationship between maternal and fetal tissues. Low expression levels or mutations of the lectin can result in pre-eclampsia. The previous crystal structure and gel filtration data show that Gal-13 dimerizes via formation of two disulfide bonds formed by Cys136 and Cys138. In the present study, we mutated them to serine (C136S, C138S and C136S/C138S), crystalized the variants and solved their crystal structures. All variants crystallized as monomers. In the C136S structure, Cys138 formed a disulfide bond with Cys19, indicating that Cys19 is important for regulation of reversible disulfide bond formation in this lectin. Hemagglutination assays demonstrated that all variants are inactive at inducing erythrocyte agglutination, even though gel filtration profiles indicate that C136S and C138S could still form dimers, suggesting that these dimers do not exhibit the same activity as wild-type (WT) Gal-13. In HeLa cells, the three variants were found to be distributed the same as with WT Gal-13. However, a Gal-13 variant (delT221) truncated at T221 could not be transported into the nucleus, possibly explaining why women having this variant get pre-eclampsia. Considering the normally high concentration of glutathione in cells, WT Gal-13 should exist mostly as a monomer in cytoplasm, consistent with the monomeric variant C136S/C138S, which has a similar ability to interact with HOXA1 as WT Gal-13.